Bidragsanalys av dimensioner och postningar - Rosenquist, Björn (2007)
An old and well known problem in sawmilling is to determine which dimensions /products those are most profitable to produce. Existing optimization models maximize the value of the log. In other words, based upon the market prices of the dimensions the models calculate the best way to split the log. Yet there is a great uncertainty if the most well paid dimensions really are the most profitable to produce. The costs of the process from lumber to sawn products are hard to determine and are therefore often left out from the optimization process.